Smart Buildings Digitalization, Two Volume Set. - Swathika, O. V. Gnana; Karthikeyan, K.; Sanjeevikumar, Padmanaban, 1978- ([Place of publication not identified] : CRC Press, 2022)
A smart building is the state-of-art in building with features that facilitates informed decision making based on the available data through smart metering and IoT sensors. This set provides useful information for developing smart buildings including significant improvement of energy efficiency, implementation of operational improvements and targeting sustainable environment to create an effective customer experience. It includes case studies from industrial results which provide cost effective solutions and integrates the digital SCADE solution. Describes complete implication of smart buildings via industrial, commercial and community platforms Systematically defines energy-efficient buildings, employing power consumption optimization techniques with inclusion of renewable energy sources Covers data centre and cyber security with excellent data storage features for smart buildings Includes systematic and detailed strategies for building air conditioning and lighting Details smart building security propulsion. This set is aimed at graduate students, researchers and professionals in building systems, architectural, and electrical engineering.
Volume I.1Building Smart Cities And Smarter Data Centers For The 21st Century Global Citizen: A Brief Study2Big Data For Smart Sensor And Intelligent Electronic Devices - Building Application3Iot Based Condition Monitoring And Automatic Control Of Rotating Machines4Design Of Cntfet Based Ternary Processor For Iot Devices5Iot Based Smart Buildings6Benefits Of Smart Building7An Approach To Realize Luxury Transit Residential Tower Aided With State-Of-Art Automation Technologies8Ann Based Overcurrent Relay Using Levenberg-Marquardt Algorithm For Smart Cities9A Neural Network Based Vector Control Scheme For Regenerative Converters To Use In Elevator Systems10Protection In Smart Building : Mini Review11A Review Of Bio-Inspired Computational Intelligence Algorithms In Electricity Load Forecasting12Arduino Based Fault Detection Scheme For Dc Microgrids13Characterizing Voltage Dependent Load And Frequency Dependent Load For Load Stability Analysis14Enabling Technologies For Smart Buildings: High Power Density Power Electronic Converters15Benefits Of Smart Meter In Institutional Building - A Case Study16Placement Of Distributed Generation (Dg) And Reconfiguration In Radial Distribution Systems- A Review In View Of Smart Building Concept17Photovoltaic System Integrated Smart Buildings: A Mini Review18Design Of Hybrid Photovoltaic And Battery Energy Storage System Using Homer Software19Ai Applications To Renewable Energy - An Analysis20Development Of Uav Based Aerial Observation Platform To Monitor Medium Voltage Networks In Urban AreasVolume II.1Nonlinear Controller For Electric Vehicles In Smart Buildings2Guidance System For Smart Building Using Li-Fi3Smart Building Automation System4Semi-Autonomous Human Detection, Tracking And Following Robot In A Smart Building5Current-Starved And Skewed Topologies Of CNTFET Based Ring Oscillators For Temperature Sensors6Efficient Data Storage With Tier Iv Data Centers In Smart Buildings7IoT Based Data Collection Platform For Smart Buildings8Sensor Data Validation For IoT Applications9Energy Economic' Appliances Scheduling For Smart Home Environment10IoT Based Smart Metering11Smart Energy Management System For Smart Homes12Design And Implementation Of Prototype For Smart Home Using Internet Of Things And Cloud13IoT Platform For Monitoring And Optimization Of The Public Parking System In Firebase14IoT Based Smart Health Monitoring System15Energy Management System For Smart Buildings16Augmented Lagrangian Model To Analyze The Synergies Of Electric Urban Transport Systems And Energy Distribution In Smart Cities17Grid Interconnected Photovoltaic Power System With LCL Filter workable For Roof Top Terracing18An Efficient ZCS Based Boost Converter For Commercial Building Applications19Implementation Of Smart Grid & Case Studies Through SBEMS / ETAP In Commercial & Official Buildings20Datalogger Aided Stand-Alone PV System For Rural Electrification21Smart Solar Modules For Smart Buildings22IoT Based Smart Contactless Hand Sanitizer Dispenser (Covid 19)
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / General; COMPUTERS / Networking / General; TECHNOLOGY / Electricity; Intelligent buildings -- Equipment and supplies; Buildings -- Communication systems; Electronic data processing -- Equipment and supplies; Electronic data processing departments; Data processing service centers; Data centers; Computation laboratories